ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI KE AMERIKA SERIKAT - HENDRI, AFIF; Suwali, Suwali (Perwira Journal of Economics & Business, 2022)
Exports are one of the main components that influence a country's Gross Domestic Product (GDP).  ountries that export more are productive countries so they have the potential to have high GDP. Indonesia ranks fourth as a coffee exporter in the world, after Colombia, Vietnam and Brazil. This research aims to (1) determine the value of Indonesian coffee exports to the United States for the period 2001 to 2020. (2) determine the factors that influence the value of Indonesian coffee exports to America for the period 2001 to 2020. This research uses a case study method with a quantitative approach. The analysis used is descriptive statistical analysis and multiple linear regression analysis. The research results show that (1) Indonesian coffee exports to America had the highest FOB value of USD 30,814,000 in 2012 and the lowest USD 41,981,000 in 2001, and an average of USD 191,115,000 during the period 2001 to 2020. (2) GDP United States real terms, the rupiah exchange rate, international coffee prices and the volume of coffee exports simultaneously influence the value of coffee exports to the United States, with an R2 value of 95.1 percent. Partially, the real GDP of the United States, the exchange rate, international coffee prices and export volume influence the value of coffee exports to the United States.